A note on concentrations of metals in cetaceans from southern Africa - Henry, John (J. Cetacean Res. Manage., 1999)
Concentrations of zinc, copper, cadmium, mercury and lead were measured by atomic absorption spectrophotometry in samples of the brain, kidney , liver and muscle tissue from 178 individuals of 323 different cetacean species (4 right whales - Eubalaena australis, 2 pygmy right whales - Caperea marginara, 3 minke whales - Balaenoptera acutorostrata, 3 Bryde's whales - B. edeni, 1 humpback whale - Megaptera novaeangliae, 1 sperm whale - Physeter macrocephalus, 11 pygmy sperm whale - Kogia breviceps, 6 dwarf sperm whales - K. simus, 1 southern bottlenose whale - Hyperoodon planifrons, 1 Cuvier's beaked whale - Ziphius cavirostris, 9 Blainville's beaked whales - Mesoplodon densirostris, 5 strap-tooth whales - M. layardii, 2 True's beaked whales - M. mirus, 3 long-finned pilot whales - Globicephala me/as, 30 Risso's dolphins - Grampus griseus, 12 bottlenose dolphins - Tursiops truncatus, 5 striped dolphins - Stenella coeruleoalba, 1 pantropical spotted dolphin - S. attenuata, 1 hump-backed dolphin - Sousa chinensis, 21 dusky dolphins - Lagenorhynchus obscurus, 1 hourglass dolphin - L. cruciger, 12 Heaviside's dolphins - Cephalorhynchus heavisidii and 43 common dolphins - Delphinus delphis). All but the hourglass dolphin were strandings or animals taken incidental to fishing operations or under scientific permit in coastal waters of South Africa or Namibia. Highest concentrations of Zn, Cu and Hg were generally found in the liver and of Cd in the kidney. Comparisons of animals pre-and post puberty indicated accumulation of hepatic mercury in the pygmy sperm whale, Risso's dolphin, dusky dolphin and common dolphin. Loss of a metal (zinc) after puberty was only shown in the common dolphin. No individual analyses exceeded proposed (human) tolerance limits for hepatic mercury and hepatic or renal cadmium